2015
DOI: 10.1007/s00296-015-3248-7
|View full text |Cite
|
Sign up to set email alerts
|

The addition of upper cervical manipulative therapy in the treatment of patients with fibromyalgia: a randomized controlled trial

Abstract: The aim of this study was to investigate the immediate and long-term effects of a one-year multimodal program, with the addition of upper cervical manipulative therapy, on fibromyalgia management outcomes in addition to three-dimensional (3D) postural measures. This randomized clinical trial with one-year follow-up was completed at the research laboratory of our university. A total of 120 (52 female) patients with fibromyalgia syndrome (FMS) and definite C1-2 joint dysfunction were randomly assigned to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 53 publications
(49 reference statements)
2
37
1
1
Order By: Relevance
“…The improvement in anxiety and quality-of-life measures is also consistent with a previous RCT which also found a significant reduction in anxiety and improvements in quality-of-life factors but no significant impact on depression ( Castro-Sanchez et al, 2011 ). In addition to this, there were consistencies with other RCTs who found improvements in state anxiety ( Bialosky et al, 2009 ; Moustafa and Diab, 2015 ) and trait anxiety ( Lopez-Lopez et al, 2015 ) but again not depression ( Moustafa and Diab, 2015 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The improvement in anxiety and quality-of-life measures is also consistent with a previous RCT which also found a significant reduction in anxiety and improvements in quality-of-life factors but no significant impact on depression ( Castro-Sanchez et al, 2011 ). In addition to this, there were consistencies with other RCTs who found improvements in state anxiety ( Bialosky et al, 2009 ; Moustafa and Diab, 2015 ) and trait anxiety ( Lopez-Lopez et al, 2015 ) but again not depression ( Moustafa and Diab, 2015 ).…”
Section: Discussionsupporting
confidence: 80%
“…These included an RCT ( Bialosky et al, 2009 ) which found that for patients receiving spinal manipulative therapy, their state anxiety positively correlated to their changes in pain sensitivity; however, there was no mention that this therapy was delivered by an osteopath specifically. For depression, another RCT ( Moustafa and Diab, 2015 ) found that after 1 hour, three times a week and for 12 weeks programme, there were significant differences between the experimental and control groups for Becks Depression Inventory (BDI) scores after a 1-year follow-up, but again, this was not specific to OMT. Licciardone et al (2013) found that patients with comorbid depression did not respond favourably to OMT; however, the impact of OMT on psychological outcomes was not specifically explored.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, two found significant differences. Moustafa and Diab found significant differences between the experimental and control groups for BDI scores (p < 0.0005) at 1-year follow-up [49]. Licciardone et al reported a significant interaction between OMT and comorbid depression (p ¼ 0.02) indicating that patients with comorbid depression did not respond favorably to OMT in their study [50].…”
Section: Resultsmentioning
confidence: 82%
“…This increased tension provides resistance against the necessary shortening and swelling of nerve fibers that accompany an action potential. This tension can give rise to local and distant signs and symptoms including neuralgias, spasticity, dizziness, bladder dysfunction, cervical and lumbar spondylosis, disk hernias, trauma to the spinal cord, and autoimmune disorders [23][24][25][26]32,33,47]. This serves as a proposed mechanism for the source of this patient's health conditions due to their resolution following sagittal cervical spinal correction.…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractic BioPhysics® (CBP®) technique is a full-spine and posture rehabilitation approach to correcting poor posture, deviation of normal spinal alignment and subluxation through incorporating mirror image® exercise, adjustments, and traction procedures [27][28][29][30][31]. CBP® has an extensive amount of quality scientific evidence supporting reliable correction of spinal and postural misalignment yielding improvements in concomitant neurological, musculoskeletal symptoms, spine movement, and patient disability levels [20,[23][24][25][26]32,33]. It seems logical to propose that improvements in spinal and neurological health may have a beneficial impact on TL.…”
Section: Page 2 Ofmentioning
confidence: 99%